Terrorists, victims and society: psychological perspectives on terrorism and its consequences - Silke, Andrew (Wiley series in the psychology of crime, policing, and law, 2003)
In today's climate, these is a powerful need for a balanced, expert and accessible account of the psychology of terrorists and terrorism. Written by an expert team of psychologists and psychiatrists, these contributors have direct experience of working with terrorists, victims and those tasked with the enormous responsibility of attempting to combat terrorism. The first section focuses on terrorists as individuals and as groups and provides a balanced and objective insight into the psychology of terrorists; what their motivations are and what keeps them involved in terrorist groups. The second section explores the huge question of the impact of terrorism; the direct and indirect affect on victims; how societies respond and how political leaders handle the threat and consequences of terrorism. The final section focuses on the question of how to respond to terrorist threat.